Impact of the major SSWs of February 2018 and January 2019 on the middle atmospheric nitric oxide abundance. (July 2021) - Pérot, Kristell; Orsolini, Yvan J.
Abstract: The Arctic middle atmosphere was affected by major sudden stratospheric warmings (SSW) in February 2018 and January 2019, respectively. In this article, we report for the first time the impact of these two events on the middle atmospheric nitric oxide (NO) abundance. The study is based on measurements obtained during two dedicated observation campaigns, using the Sub-Millimetre Radiometer (SMR) aboard the Odin satellite, measuring NO globally since 2003. The SSW of February 2018 was similar to other, more dynamically quiet, Arctic winters in term of NO downward transport from the upper mesosphere–lower thermosphere to lower altitudes (referred to as energetic particle precipitation indirect effect EPP-IE). On the contrary, the event of January 2019 led to one of the strongest EPP-IE cases observed within the Odin operational period. Important positive NO anomalies were indeed observed in the lower mesosphere–upper stratosphere during the three months following the SSW onset, corresponding to NO volume mixing ratios more than 50 times higher than the climatological values. These different consequences on the middle atmospheric composition are explained by very different dynamical characteristics of these two SSW events. Highlights: Different impact of the 2018 and 2019 SSWs on the NO distribution observed by SMR. Only the 2019 SSW event was characterised by a marked elevated stratopause. It led to an important increase in NO concentration in the upper stratosphere. This was one of the strongest EPP indirect effect cases observed since 2003.